Modelo i-META de monitoreo de actividades de autoevaluación y acreditación en la Escuela Académica Profesional de Ingeniería Metalúrgica – UNMSM - Lovera Dávila, Daniel (2012)
The guidelines for preparing the accreditation project for university professional careers are found in a working document prepared by the Central Office for Academic Quality and Accreditation, which provides guidance to the Internal Committees of each of the UNMSM professional careers. The Accreditation Project Structure for the Professional Academic School of Metallurgical Engineering (EAPIM), follows the requirements of the CONEAU Guide to Accreditation of University Professional Careers. In this framework, the studies for the systematization of standards allowed us to propose the i-Meta Model as the educational project that identifies the organizational culture, infrastructure, interest groups and by grouping the criteria into 7 plans, 7 processes, 7 programs and 7 systems; in a way that allows for quick and approximate monitoring and / or auditing of each academic unit where the self-evaluation and improvement plan has been developed. The i-Meta Matrix shows the level of standards of the School of Metallurgical Engineering (30% at the medium level and 70% at the low level), indicating the need to develop intensive improvement actions in the short, medium and long term, to reach the level in the standards and achieve university accreditation.